Contemporary Cleaning of the Root Canal System. Issue 4 (December 2020) - Barnes, Justin J.; Blum, Igor R.
This article provides a contemporary synopsis of effective cleaning of the root canal system, an essential stage of root canal treatment. It provides a clinical update on the current state of knowledge on cleaning of the root canal system, and presents an outline of essential theory and practical tips for achieving effective and safe cleaning of the root canal system.